Co-application of nanosized halloysite and biochar as soil amendments in aided phytostabilization of metal(-oid)s-contaminated soil under different temperature conditions - Radziemska, Maja; Gusiatin, Zygmunt M; Kumar, Vinod; Brtnicky, Martin (Chemosphere, 2022)
The threat posed by the degradation of the soil environment by metal (-oid)s has been lead to the improvement of existing or search for new remediation methods; in this case, the application of environmentally friendly nanomaterials falls into this trend. The study applied a technique of aided phytostabilization for the immobilization of metal (-oid)s in soil with the application of nanosized halloysite and biochar (nBH), along with Lolium perenne L. Its effectiveness was assessed in terms of changing temperature conditions (16 cycles of freeze and thaw cycles, (FTC)) on the content of As, Cu, Pb and Zn in the soil, roots, and above-ground parts of the tested plant, chemical fraction distributions of metal (-oid)s and their stability (based on reduced partition index, Ir). The biomass yield in nBH-amended soil was 2-fold higher compared to control soil, but it decreased by 1.6-fold after FTC. nBH facilitated more bioaccumulation of As, Pb and Zn than Cu in plant roots, before than after FTC. nBH increased pH in phytostabilized soil, but it was not affected by changing FTC. In soil nBH-phytostabilized total concentration of metal (-oid)s significantly decreased compared to control soil, for As and Cu below permissible value, regardless of FTC. Soil amendment and changing temperature conditions affected metal (-oid)s redistribution in soil. As a result, the stability of As increased from 0.50 to 0.66, Cu from 0.49 to 0.52, Pb from 0.36 to 0.48 and Zn from 0.39 to 0.47. These findings suggest that nBH can immobilize metal (-oid)s in phytostabilized soil under changing temperature conditions.
Keywords: Metals, Heavy; Immobilization; Temperature; Aided phytostabilization; biodegradace; jíl; Soil Pollutants; látky znečišťující půdu; teplota; půda; Biodegradation, Environmental; Clay; těžké kovy; Nanoremediation; Freeze-thaw cycle; Soil; Charcoal; dřevěné a živočišné uhlí; Soil risk minimization